Neutrophil Gelatinase-Associated Lipocalin (NGAL), Pro-Matrix Metalloproteinase-9 (pro-MMP-9) and Their Complex Pro-MMP-9/NGAL in Leukaemias - Bouchet, Sandrine (MDPI, 2014)
Matrix metalloproteinase (MMP)-9 and neutrophil gelatinase-associated lipocalin (NGAL) have gained attention as cancer biomarkers. The inactive zymogen form of MMP-9 (pro-MMP-9) also exists as a disulphide-linked heterodimer bound to NGAL in humans. Leukaemias represent a heterogeneous group of neoplasms, which vary in their clinical behavior and pathophysiology. In this review, we summarize the current literature on the expression profiles of pro-MMP-9 and NGAL as prognostic factors in leukaemias. We also report the expression of the pro-MMP-9/NGAL complex in these diseases. We discuss the roles of (pro)-MMP-9 (active and latent forms) and NGAL in tumour development, and evaluate the mechanisms by which pro-MMP-9/NGAL may influence the actions of (pro)-MMP-9 and NGAL in cancer. Emerging knowledge about the coexpression and the biology of (pro)-MMP-9, NGAL and their complex in cancer including leukaemia may improve treatment outcomes.